Vibration Analysis on Centrifugal Pump in UTHM Biodiesel Plant - Taranjit Singh A/L Bahjan Singh; Nurhafizzah Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Vibration is the most common problem in rotating machinery and equipment and these problems need to be investigated to determine the possible causes and recommended actions to minimize these vibration problems. This research investigates vibration issues in centrifugal pumps at UTHM Biodiesel Plant, focusing on vibration analysis based on ISO 10816 and ISO 2372 (severity chart) standards. The study analyzes vibration severity at four bearing locations (motor and pump) in three directions (horizontal, axial, vertical) on pumps P001, P202, and P219 using a vibration analyzer. The condition of the pump is assessed using the vibration velocity (mm/s), referring to the severity chart. Fault diagnosis, including misalignment, unbalance, and looseness, is conducted via Fast Fourier Transform (FFT) data, interpreting peak properties and harmonics using Vibrograph software. Results show that pumps P001 and P202 exceed safe vibration limits, indicating significant misalignment and looseness requiring immediate maintenance. The pump P219 is in good condition but needs alignment maintenance due to parallel misalignment. The study emphasizes early diagnostics of potential failures, enabling cost- and time-effective maintenance while ensuring operational safety and reliability.